2022
DOI: 10.1021/acsmacrolett.2c00205
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Polysaccharide−Polypeptide Conjugates via a Biphasic Solution Ring-Opening Polymerization

Abstract: Polysaccharide−polypeptide conjugates have gained a broad interest in mimicking the structure and bioactivity of peptidoglycans or proteoglycans for biomedical applications. Efficient and precise preparation of the conjugates is challenging and unresolved, mainly because of the mismatched solubility between polysaccharide initiators and N-carboxyanhydrides (NCAs), which frequently results in competing side reactions and oligomeric polypeptide chain. Herein, we report a facile and efficient strategy to prepare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Later, they prepared a series of chitosan‐ poly( L ‐glutamic acid) conjugates (CS‐g‐Es) by a biphasic solution ring‐opening polymerization (bsROP) and subsequent hydrolysis. [ 67 ] CS‐g‐Es were coated on polydopamine (PDA) modified polydimethylsiloxane (PDMS) surface with the assistance of dopamine (DA). The antibacterial adhesion and antibiofilm growth of the CS‐g‐E coatings were enhanced by elongating the poly( L ‐glutamic acid) chain length.…”
Section: Antibacterial Polymer Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, they prepared a series of chitosan‐ poly( L ‐glutamic acid) conjugates (CS‐g‐Es) by a biphasic solution ring‐opening polymerization (bsROP) and subsequent hydrolysis. [ 67 ] CS‐g‐Es were coated on polydopamine (PDA) modified polydimethylsiloxane (PDMS) surface with the assistance of dopamine (DA). The antibacterial adhesion and antibiofilm growth of the CS‐g‐E coatings were enhanced by elongating the poly( L ‐glutamic acid) chain length.…”
Section: Antibacterial Polymer Coatingsmentioning
confidence: 99%
“…In addition, cationic brush‐like chitosan‐poly( L ‐lysine) conjugates (CS‐g‐Ks) were prepared by Tang et al . [ 67 ] CS‐g‐Ks modified PDMS surfaces were prepared by PDA co‐deposition method. Both killing efficacy and inhibition of biofilm growth of CS‐g‐K coatings were improved by increasing the cationic polypeptide chain length that >99.9% killing efficacy and ≤ 2.8% biofilm growth can be readily achieved (Figure 4a).…”
Section: Antibacterial Polymer Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In most cases, the preparation process is performed in organic solvents. [34][35][36][37] For example, Du et al proposed a one-pot opento-air ROP of N-carboxyanhydride (NCA)-induced self-assembly for the preparation of poly(ethylene oxide)polyphenylalanine vesicles in tetrahydrofuran at 10 °C. 38 Duro-Castano and Battaglia et al reported the one-step synthesis of oxidationsensitive polypeptide-based nanoparticles in dimethyl sulfoxide (DMSO) by ROPISA of methionine NCA.…”
Section: Introductionmentioning
confidence: 99%
“…The desired polymerization of NCA outpaces various side reactions including the water-induced side reactions, 33,38,43,45 enabling the preparation of well-defined polypeptides even in the presence of an aqueous phase. 38,43,48 Additionally, the accelerated polymerization allows the efficient synthesis of polypeptides with versatile architectures, 31,32,35,42,49 high MWs, 32,34,42,46 and predictable multiblock sequences, 39,45 which is difficult, if not impossible, to obtain with conventional polymerization methods.…”
Section: Introductionmentioning
confidence: 99%